2021
DOI: 10.1111/jth.15220
|View full text |Cite
|
Sign up to set email alerts
|

Management of elective procedures in low von Willebrand factor patients in the LoVIC study

Abstract: Background Most individuals with mild to moderate reductions in plasma von Willebrand factor (VWF) levels do not demonstrate increased bleeding. However, some patients with plasma VWF levels of 30–50 IU/dl do have a significant bleeding phenotype. Management of these “low VWF” patients, who may have significant bleeding scores >10, around times of elective procedures continues to pose a common clinical challenge because of a lack of evidence. Objective To investigate the safety and efficacy of different peripr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…12,59 Consistent with these findings, Doherty et al went on to use desmopressin AE TA to manage 99 elective dental and minor surgical procedures. 58 Even though all these low VWF patients had significant bleeding histories, bleeding complications were observed in only one single dental extraction. 58 Cumulatively, these laboratory and clinical data therefore suggest that desmopressin has an important role to play in the management of low VWF.…”
Section: Treatment Of Low Vwfmentioning
confidence: 94%
See 2 more Smart Citations
“…12,59 Consistent with these findings, Doherty et al went on to use desmopressin AE TA to manage 99 elective dental and minor surgical procedures. 58 Even though all these low VWF patients had significant bleeding histories, bleeding complications were observed in only one single dental extraction. 58 Cumulatively, these laboratory and clinical data therefore suggest that desmopressin has an important role to play in the management of low VWF.…”
Section: Treatment Of Low Vwfmentioning
confidence: 94%
“…[55][56][57] Doherty et al recently reported on the management of elective procedures in adult low VWF patients in the LoVIC study. 58 This retrospective review included 160 invasive procedures (40 dental, 109 minor, and 11 major procedures) performed in 60 patients. Notably, these low VWF patients all had abnormal ISTH BAT scores, with 21/60 (35%) patients having BAT scores greater than 10.…”
Section: Treatment Of Low Vwfmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Desmopressin (DDAVP) trials were performed in 75 patients with low VWF. 15 In brief, DDAVP (0.3 μg/kg; maximum dose capped at 27 μg/kg) was administered IV, and blood samples were drawn for VWF:Ag, VWF:RCo, and FVIII:C at baseline (T0), 1 hour (T+1), and 4 hours (T+4). In a subset of 24 patients, additional samples were drawn at 24 hours (T+24).…”
Section: Methodsmentioning
confidence: 99%
“…As part of a prospective study, 40 dental procedures (mostly single tooth extractions) were performed under local hemostatic measures in addition to systemic administration of tranexamic acid (1 g/3 × days) in 25% of the cases and desmopressin (0.3 μg/kg BW) in 72.5% of the cases. As a result, only 10% of the treated patients showed post-interventional bleeding events [ 13 ].…”
Section: Literature Review On Bleeding Disorders In Dentistrymentioning
confidence: 99%